A Educação Infantil frente aos diferentes padrões de sono e vigília de crianças de 0 a 3 anos: dilemas e equívocos - Santos, Maria Goreti Miguel (2006)
Sleep is an activity that has remained unchanged in day care centers which deal with infants up to the age of 3 years old. This paper aimed at investigating how educators of public schools for children dealt with the different sleep and/or vigil rhythms of these children; nevertheless, an analysis of the collected data showed us that there were other practices that have also remained unchanged and that are part of the institutional routine of these children. It is, therefore, of vital importance to re-examine the educational background of those professionals who are responsible for young children. In fact, the data collected shows that there is a waste of time that could be used in a more productive way in terms of how these children develop and learn. As time is not used adequately, there is no progress and the objectives of Children Education tend to be minimized. We hope results shown here will make it possible to debate in depth such an important issue which has not been properly studied yet